Kesantunan Berbahasa dalam Narasi Dialog Cerita Rakyat Jawa Tengah pada Kanal YouTube Gromore Studio Series (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
Politeness in language use is a crucial aspect that has become an integral part of Indonesian culture. Politeness norms almost always serve as a reference in every speech act. Since politeness is culturally embedded, what is considered polite in one society may not be perceived the same in another. The YouTube channel Gromore Studio Series presents Central Javanese folktales with dialogic narration rich in linguistic expressions; however, it has not been widely analyzed from the perspective of language politeness. This study aims to analyze language politeness in six folktale videos on the channel using a descriptive qualitative method with content analysis techniques. The data were analyzed based on Leech’s (1983) six maxims of politeness. The results show that most dialogues adhere to the principles of politeness, with 106 data conforming and 38 violating them. The most frequently observed maxim is the Agreement Maxim (28 instances), followed by the Approbation Maxim (26 instances), while the least frequent is the Obligation of O to S Maxim (8 instances). The application of language politeness in these folktales emphasizes harmony, respect, and solidarity among characters, while violations occur less frequently. This study provides valuable insights for research in pragmatic linguistics, the development of culturally based educational content, and the understanding of language politeness in digital media contexts.